Drosophila versus Mycobacteria: A model for mycobacterial host-pathogen interactions. - Marshall, E.K.P.; Dionne, M.S. (Molecular Microbiology, 2022)
Animal models have played an essential role in understanding the host-pathogen interactions of pathogenic mycobacteria, including the Mycobacterium tuberculosis and emerging nontuberculous mycobacteria (NTM) species such as M. avium and M. abscessus. Drosophila melanogaster has become a well-established model for the study of innate immunity and is increasingly being used as a tool to study host-pathogen interactions, in part due to its genetic tractability. The use of D. melanogaster has led to greater understanding of the role of the innate immune system in response to mycobacterial infection, including in vitro RNAi screens and in vivo studies. These studies have identified processes and host factors involved in mycobacterial infection, such as those required for cellular entry, those required to control or resist non-pathogenic mycobacteria, or factors that become dysregulated as a result of mycobacterial infection. Developments in genetic tools for manipulating mycobacterial genomes will allow for more detailed studies into how specific host and pathogen factors interact with one another by using D. melanogaster; however, the full potential of this model has not yet been reached. Here we provide an overview of how D. melanogaster has been used to study mycobacterial infection and discuss the current gaps in our understanding.